If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying n + 6 + -2 = 1 Reorder the terms: 6 + -2 + n = 1 Combine like terms: 6 + -2 = 4 4 + n = 1 Solving 4 + n = 1 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + n = 1 + -4 Combine like terms: 4 + -4 = 0 0 + n = 1 + -4 n = 1 + -4 Combine like terms: 1 + -4 = -3 n = -3 Simplifying n = -3
| 2+c-3=3 | | X^4-3x^2+4x-6=0 | | F(x)=-3x+5 | | (cd+2)+cd-4= | | x^2-(m+1)x-5=0 | | (8x+4)=(5x+2) | | Sinx=0.75 | | 2a+16+b=18+b | | 9x+26x^2=3 | | 6y-2=2y+7 | | 8+3x+x=20 | | 58474+46274= | | t=5(2)+3(4) | | 15-3x+2-8x=39 | | 58584839748375097+85574758475398= | | 7x-5y+(-3x+-4y)= | | M(m+2)=2 | | 5x-13=-25 | | 13y^2-4y-9=0 | | 4w=w-2 | | 13y^2-4y+9=0 | | x^2+y^2=4x-4y-6 | | 40+7x=0 | | 0.3*x+x^2=0.3x^3 | | (3c-2)(2c+5)=0 | | x^2+y^2-4x+4y+6=0 | | (45x^6)-(36y^2)-144=0 | | (45x^2)-(36x^2)-144=0 | | (36x^2)+(36x^2)-144=0 | | 4v-3=-5 | | (y^2-6)+(90)+(y+1)=180 | | 13x-10+12x=180 |